Mind The Gap: Commitment Attributions in Argumentative Exchanges - Haro Marchal, Amalia (Informal Logic)

(untitled) (Informal Logic, 2025)
Argumentation, as a specific type of speech act, involves an exchange of meaning among its participants, yielding illocutionary effects consisting in the production of changes in participants’ dialectical entitlements and obligations. The production of these illocutionary effects hinges on the joint construction by the speaker and the interlocutor of the meaning of the speaker’s utterance. However, the speaker’s meaning does not always coincide with the interlocutor’s interpretation. This paper argues that this gap has crucial implications for the evaluation of argumentation. Specifically, it explores the consequences of this gap in cases involving commitment attributions, taking the straw man fallacy as a case of study.